Numerical Simulation of Churn and Annular Transient Flows - Savagnago V.* (2022)
© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.Two-phase gas-liquid flows are often present in many applications. The correct simulation of these flows is crucial in industrial projects, which require detailed information about flow parameters, such as pressure gradient, void fraction, and heat transfer coefficients. Simulation of complex patterns, as churn and annular flow, have many simplifications. Most models for pattern and flow properties determination are based on empirical data, which have limited applications. Processes involved in these patterns are not completely understood, so mechanistic models usually are not satisfying. This work aims to investigate the churn and annular patterns, and the transition between them using a hybrid method, which couples a two-fluid model with the volume of fluid (VOF) with interfacial compression. Results obtained for void fraction and pressure gradient are compared to experimental data and the influence of the maximum Courant number in the simulations results is evaluated. The method allows the visualization of gas-liquid flow phenomena, such as the presence of liquid filaments in the gas core and interfacial disturbance waves. Simulations provide good results for the void fraction, with a maximum relative error of 6,39% compared to experiments. The pressure gradient in the flow is significantly overestimated, which may be a result of the simulation of an incomplete geometry, that does not represent the entire experimental test sections.